2004
DOI: 10.1007/s10143-004-0340-y
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone-receptor index in meningiomas: correlation with clinico-pathological parameters and review of the literature

Abstract: For recurrent and untreatable meningiomas alternative therapies, such as anti-progesterone treatment, have been sought. However, the few clinical studies have not determined progesterone receptor (PgR) expression in most cases, and studies correlating quantitative PgR expression (PgR index) with clinico-pathological variables are scarce. The aim of our study was to assess the PgR indices in a consecutive series of meningiomas and correlate these values with clinico-pathological parameters. We analyzed immunohi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
58
2
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(74 citation statements)
references
References 55 publications
12
58
2
2
Order By: Relevance
“…16 Actually, progesterone receptor positivity has been reported to negatively correlate with tumor grade by many authors. [16][17][18][19] In other words, there is a reduction of progesterone receptors from WHO grade I to grade II and a progesterone receptor negativity in WHO grade III tumors. [16][17][18][19] The reason why RM presents similarly to benign meningioma is not clear.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Actually, progesterone receptor positivity has been reported to negatively correlate with tumor grade by many authors. [16][17][18][19] In other words, there is a reduction of progesterone receptors from WHO grade I to grade II and a progesterone receptor negativity in WHO grade III tumors. [16][17][18][19] The reason why RM presents similarly to benign meningioma is not clear.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…[16][17][18][19] In other words, there is a reduction of progesterone receptors from WHO grade I to grade II and a progesterone receptor negativity in WHO grade III tumors. [16][17][18][19] The reason why RM presents similarly to benign meningioma is not clear. However, this may be because of the fact that the rhabdoid morphology can only present in a part of the tumor, though most RMs have high A B C Fig 1. A 64-year-old woman presenting with memory disturbances.…”
Section: Clinical Presentationmentioning
confidence: 99%
“…However, such expression may not be considered an independent prognostic marker (3) . Some authors have confirmed the quantitative expression of progesterone receptors in studies involving a variety of meningioma cases, thereby suggesting that it is possible to conduct clinical trials with antiprogesterone therapy (10) . Although many meningiomas have a good prognosis after treatment, there is still great controversy regarding the best means of management, which requires an understanding of the risks and benefits of radiotherapy and surgical treatment, as well as of the potential long-term risks (3) .…”
Section: Discussionmentioning
confidence: 93%
“…Nevertheless, postoperative radiotherapy has been recommended for the prevention of local recurrence (3,10) , especially when resection is partial or when histology suggests malignancy (10) . The efficacy of chemotherapy for intracranial meningioma is supposedly low, since no satisfactory results have been shown for isolated cases (3,10) . Several studies have demonstrated a correlation between high expression of progesterone receptors and lower histological level, low recurrence frequency and better prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Progesterone and androgen receptors are expressed on approximately two thirds of meningiomas and estrogen receptors are expressed on approximately 10% (Wen et al, 2009). Progesterone receptors are predominantly expressed in benign meningiomas with low proliferation indices and they are infrequently expressed in atypical and malignant meningiomas (Wolfsberger et al, 2004). Again, data for malignant meningiomas specifically is limited, likely due to their scarcity.…”
Section: Hormonal Therapymentioning
confidence: 99%